2015
DOI: 10.1016/j.jaapos.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Dichoptic movie viewing treats childhood amblyopia

Abstract: Background Contrast-balanced dichoptic experience with perceptual-learning tasks or simple games has been shown to improve visual acuity significantly in amblyopia. However, these tasks are intensive and repetitive, and up to 40% of unsupervised patients are noncompliant. We investigated the efficacy of a potentially more engaging movie method to provide contrast-balanced binocular experience via complementary dichoptic stimulation. Methods Eight amblyopic children 4–10 years of age were enrolled in a prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
109
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 90 publications
(119 citation statements)
references
References 23 publications
7
109
1
2
Order By: Relevance
“…15−17 The magnitude of improvement was more similar to the 2 lines found with dichoptic movie treatment, 19 suggesting that a larger improvement may be owing to better compliance with our adventure game. Indeed, 85% (23 of 27) of children played at least 75% of prescribed treatment compared with 44% (20 of 45) in the Tetris game study.…”
Section: Discussionmentioning
confidence: 71%
“…15−17 The magnitude of improvement was more similar to the 2 lines found with dichoptic movie treatment, 19 suggesting that a larger improvement may be owing to better compliance with our adventure game. Indeed, 85% (23 of 27) of children played at least 75% of prescribed treatment compared with 44% (20 of 45) in the Tetris game study.…”
Section: Discussionmentioning
confidence: 71%
“…Only 22% of our children achieved greater than 75% compliance, suggesting that compliance should be reviewed more frequently and games need to be more appealing such as more engrossing children’s games, binocular first person action games, 18 and binocular movie viewing. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Most of the children in the present study who showed visual acuity improvement with treatment were participants in an ongoing study of a binocular amblyopia treatment based on the protocol originally described by Hess et al 2,13,15,33,41 Previous reports of amblyopic adults who participated in similar binocular treatment protocols reported correlated improvements in contrast ratio balance and amblyopic eye visual acuity. 2,12,33,38,4245 However, prior studies of amblyopic children who participated in binocular treatment have consistently failed to show improvement in contrast ratio balance despite improvements in visual acuity. 13,14,16,46 These earlier studies in amblyopic children relied on the dichoptic global motion coherence task to quantify severity of suppression.…”
Section: Discussionmentioning
confidence: 99%